Anti-SLAPP sebagai Strategi NDC dalam Perlindungan Hutan Zero Deforestation - Pertiwi, Ella Paramitha; Effendy, Muhammad Alim Multazam; Taufik, Moh.; Yakin, Moh Ainul (Universitas Muhammadiyah Ponorogo, 2025)
Indonesia has very diverse natural resources, especially the abundant forest wealth. But in reality, forest wealth is declining due to deforestation. This contradicts Article 28 H paragraph (1) of the 1945 Constitution of the Republic of Indonesia which states that people need to fulfil their right to a good and healthy environment. The research was conducted using normative juridical method through statutory, case study and conceptual approaches that produced qualitative data through literature study. This research found the fact that there is no regulation that discusses the implementation of Nationally Determined Contributions (NDC) in Indonesia and there are still many cases of criminalisation due to deforestation cases. Therefore, it is necessary to embody the NDC in the Anti-SLAPP regulation to realise Zero Deforestation-based forest protection in Indonesia.